On the Uniformity of Distribution of the ElGamal Signature. - Shparlinski, Igor E.
We show that, under some natural conditions,the pairs (r,s) produced by the ElGamal signature scheme are uniformly distributed. In particular this implies that values of r and s are not correlated. The result is based on some new estimates of exponential sums.
Keywords: ElGamal signature scheme; Exponential sums; Uniform distribution